The management of dental fracture on tooth 61 in a child with attention deficit hyperactivity disorders - Veranica Veranica; Mochamad Fahlevi Rizal (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Attention deficit hyperactivity disorder (ADHD) is often characterized as a neurobehavioral developmental disorder, impaired concentration, impaired motor skills, impulsivity, and hyperactivity, and also diagnosed as psychiatric disorders. Children with ADHD would have a tendency of the traumatized anterior teeth because of their hyperactive behavior. Dental trauma is actually one of factors causing the damages of the deciduous teeth and the permanent teeth. Dental and mouth care for children with special needs, such as children with ADHD, requires special treatment. Purpose: This study is aimed to report the case management of the dental fracture of the tooth 61 in a child with ADHD. Case: A four-year old girl suffered from both ADHD and dental fracture involving the dentin of the tooth 61. Case management: The examination of the patient with dental fracture consists of emergency examination and further investigation. The emergency examination covers general condition and clinical situation. Based on the dental radiographic assessment, it is known that the dental fracture of the tooth 61 had involved the dentine, the resorption had reached 1/3 of the apical teeth and the permanent teeth had been formed. The application of calcium hydroxide on the opened dentin is aimed to improve the formation of the secondary dentin served as pulp protector. Next, the restoration of the traumatized teeth used compomer since it does not only meet all the aesthetic requirements, but it also releases fluoride. Management of the patient’s behavior with ADHD was conducted by non-pharmacological method; tell show do (TSD) method combined with restrain method. Conclusion: It can be concluded that the application of calcium hydroxide and the restoration of the teeth with compomer could provide maximum results through the combination of TSD and restrain methods that can effectively increase the positive value to replace the negative behaviors that have been formed.Latar belakang: Gangguan pemusatan perhatian-hiperaktivitas (GPPH), sering dikarakteristikan sebagai gangguan perilaku, gangguan konsentrasi, motorik, impulsif, dan hiperaktivitas dan didiagnosa sebagai gangguan psikiatrik. Anak penderita GPPH mempunyai kecenderungan mengalami trauma gigi anterior karena perilaku hiperaktivitasnya. Trauma gigi anak merupakan salah satu penyebab kerusakan pada gigi sulung maupun pada gigi tetap. Perawatan gigi dan mulut pada anak berkebutuhan khusus seperti anak penderita GPPH memerlukan pendekatan khusus. Tujuan: Makalah ini bertujuan melaporkan kasus penatalaksanaan fraktur gigi 61 pada anak dengan GPPH. Kasus: Seorang anak perempuan berusia 4 tahun menderita GPPH dan mengalami fraktur yang melibatkan dentin pada gigi 61. Tatalaksana kasus: Pemeriksaan pasien yang mengalami fraktur terdiri dari pemeriksaan darurat dan pemeriksaan lanjutan. Pemeriksaan darurat meliputi keadaan umum dan keadaan klinis. Penilaian radiografis memperlihatkan fraktur gigi 61 melibatkan dentin, resopsi mencapai 1/3 apikal dengan benih gigi tetap telah terbentuk. Aplikasi kalsium hidroksida pada dentin terbuka bertujuan untuk meningkatkan pembentukkan dentin sekunder dan berfungsi sebagai pelindung pulpa. Restorasi gigi yang mengalami trauma menggunakan kompomer karena selain memenuhi persyaratan estetik juga melepaskan fluor. Penanganan manajemen perilaku pada anak GPPH dilakukan dengan metode non farmakologi, yaitu melalui pendekatan tell show do (TSD) yang dikombinasikan dengan metode restrain. Kesimpulan: Aplikasi kalsium hidroksida dan restorasi gigi dengan kompomer memberikan hasil maksimal, melalui kombinasi TSD dan restrain, efektif meningkatkan nilai positif untuk menggantikan perilaku negatif yang telah terbentuk.